2009
DOI: 10.1111/j.1464-5491.2009.02820.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in yield and effects of screening intervals during 17 years of a large UK community‐based diabetic retinopathy screening programme

Abstract: Over time the risk of late diagnosis of STDR decreased, possibly attributable to earlier diagnosis of less severe retinopathy, decreasing risk factors and systematic screening. Screening intervals of up to 24 months should be considered for lower risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 19 publications
4
75
2
4
Order By: Relevance
“…Another study of 1,322 patients with type 2 diabetes did not observe any patients developing severe non-proliferative or proliferative retinopathy by 3 year follow-up if they had no retinopathy at baseline [24]. Misra et al [12], examining a larger sample, found that patients were no more likely to have referable retinopathy or maculopathy if they were screened every 18-24 months compared with every 12-18 months. Our results suggest that those patients who miss 1 or more years of screening represent a high-risk group with a greater chance of re-attending having developed retinopathy.…”
Section: Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study of 1,322 patients with type 2 diabetes did not observe any patients developing severe non-proliferative or proliferative retinopathy by 3 year follow-up if they had no retinopathy at baseline [24]. Misra et al [12], examining a larger sample, found that patients were no more likely to have referable retinopathy or maculopathy if they were screened every 18-24 months compared with every 12-18 months. Our results suggest that those patients who miss 1 or more years of screening represent a high-risk group with a greater chance of re-attending having developed retinopathy.…”
Section: Characteristicmentioning
confidence: 99%
“…Around 79% of individuals invited for diabetic eye screening in England took up the offer of screening in 2010/2011 [4]. Patients who do not attend for screening have poorer HbA 1c and blood pressure control [7] and have been diagnosed with diabetes for longer [7,8], all of which are risk factors for developing retinopathy [8][9][10][11][12][13][14][15]. These observations suggest that patients who do not attend for eye screening might be at increased risk of diabetic eye disease.…”
Section: Introductionmentioning
confidence: 99%
“…The Scottish Intercollegiate Guidelines Network (SIGN) 21 reported that patients with diabetes with no detected retinopathy could be screened every 2 years, with all others being screened at least annually. There have been a number of studies [22][23][24][25] that have modelled the possible effect of moving from annual to 2-3-year intervals in patients with type 1 and type 2 diabetes using incidence data from screening programmes in Iceland, Liverpool and Norwich. In 2007, Olafsdottir and Stefansson 26 reported the 10-year experience of biennial eye screening in patients with diabetes without retinopathy from Iceland, concluding that this seems to be safe and effective.…”
Section: Introductionmentioning
confidence: 99%
“…Although improved management of risk factors and advances in treatment modalities for diabetic retinopathy have contributed to reducing the risk of blindness from this pathology [2][3][4], type 2 diabetes per se has been continuously increasing in Asian populations [5,6]. The report from the International Diabetes Federation estimated that people with diabetes in the Asian Pacific region will increase from 137 million in 2010 to 214 million by 2030 [7].…”
Section: Introductionmentioning
confidence: 99%